Specialized Content Knowledge Lower Secondary School Teachers on Quadrilaterals - Pagiling, Sadrack Luden; Nur'aini, Khumaeroh Dwi (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2022)
The teachers' knowledge of specific content has a positive relationship with the students' mathematics achievement. Mathematics teachers must have an appropriate level to ensure mathematics learning effectively. The quadrilateral is one of the essential contents in geometry. However, many teachers did not successfully deliver and teach this content in classroom instruction. Therefore, this qualitative study explores the specialized content knowledge of lower secondary teachers in defining and classifying quadrilaterals. Four teachers, two male and two female teachers, were recruited to become participants in this work. All participants have similar teaching experience and do not hold an educator certificate. A test and semi-structured interviews were assigned to obtain specialized content knowledge of the teachers on quadrilaterals. The interview data were analyzed in three stages: data condensation, data presentation, and conclusion drawing. The findings show that only one teacher understands hierarchically in defining and classifying quadrilaterals, two teachers are at the partial prototype level because they cannot see the hierarchical relationship between the quadrilaterals, and another teacher is at the prototype understanding level because it relies on the prototype of quadrilaterals' shape. These findings suggest that lower secondary teachers' special content knowledge of quadrilateral needs to be strengthened through workshops and training professional development.